EFEKTIVITAS BERBAGAI PELARUT ORGANIK PADA EKSTRAKSI SENYAWA FUNGSIONAL BERAS HITAM - Nurhidajah Nurhidajah; Ali Rosidi; Yunan Kholifatuddin Sya'di; Diode Yonata (AGROINTEK, 2022)
Functional compounds from black rice were extracted conventionally using organic solvents, namely ethanol-distilled water and ethanol-distilled water-acid (acetic acid and a mixture of lactic acid and acetic acid) along with distilled water as control. The effectiveness of each solvent was determined by analysis of functional compounds contents (anthocyanin content, flavonoids, total phenolic, and antioxidant activity), pH value, and the resulting color characteristics. The ethanol-distilled water-citric acid solvent produced significantly higher levels of anthocyanin, total phenolic, and antioxidant activity, with the lowest extraction pH, but produced fewer flavonoids. Red-purple black rice extract has the lowest brightness. The ethanol-distilled water-citric acid solvent has the best effectiveness in the extraction of black rice functional compounds.